Exploiting channel and interface heterogeneity for rate separating channel assignment in IEEE 802.11 wireless multimedia sensor networks - Tae-Sung Kim; Sok-Hyong Kim; Young-Yong Kim (International Journal of Distributed Sensor Networks)
In wireless multimedia sensor networks (WMSNs), disaster control and public safety are crucial issues that focus on emergency management, rescue, and emergency medical services. For high data rate requirement of WMSNs, the IEEE 802.11 specification can be used for the radio interface of sensor nodes, and the nodes can be equipped with multiple 802.11 radios to utilize multiple channels and link data rates. In practical IEEE 802.11 WMSNs, a link shows different link qualities depending on the operating channels and interfaces between two nodes, called channel and interface heterogeneity . In multirate WMSNs, low-rate links severely degrade the capacity of high-rate links, known as rate anomaly . In this article, we propose a novel channel assignment protocol, heterogeneity-aware mesh (HMesh), to address both rate anomaly mitigation and the channel and interface heterogeneity in real IEEE 802.11 WMSNs. HMesh constructs a tree-based WMSN using the proposed channel assignment and routing metric and the heuristic channel assignment algorithm. With the metric and heuristic algorithm, HMesh separates different data rate links by considering the channel and interface heterogeneity. Through extensive simulations and experiments on our IEEE 802.11 WMSN test bed, we demonstrate that HMesh significantly outperforms existing channel assignment protocols in IEEE 802.11 WMSNs.